Pengaruh Strategi Copy The Master Melalui Media Audiovisual Terhadap Keterampilan Menulis Puisi Siswa Kelas XI SMA Negeri I Cihara - Yudiono, Aday (Jurnal Artikula, 2025)
This study was conducted using the copy the master strategy of class XI students in the 2024/2025 Academic Year as the population. The samples taken were classes XI.1 and XI.2 with a total of 64 students. The sampling technique used Random Sampling. The data obtained showed that the average posttest score for the experimental class was 87.53 with a standard deviation of 6.064, while the average posttest score for the control class was 69.72 with a standard deviation of 2.774. The results of the independent sample t-test showed a sig value (2-tailed) of 0.000, which is smaller than 0.005.Thus, the copy the master strategy is declared effective in improving poetry writing skills compared to the thik, talk, write learning strategy applied in the control class. A significant difference can be seen from the average posttest score, where the experimental class obtained an average of 87.53, while the control class only got 69.72. Based on this data analysis, it can be concluded that the application of the copy the master strategy has a greater positive impact on students' poetry writing skills compared to the think, talk, write strategy which is considered sufficient in learning strategies